VDSL and G.fast Vectoring and the impact on VULA - Thomas Plückebaum; Stephan Jay; Karl-Heinz Neumann (International Telecommunications Society (ITS), 2014)
VDSL and G.fast Vectoring are transmission technologies over copper access line pairs enabling the transmission of higher bandwidth to the end customers, but harm the infrastructure based competition using physical unbundled copper lines. Thus regulators have to decide between infrastructure based competition of physical unbundling against earlier broadband rollout meeting the DAE goals in time and bandwidth, while pure fibre based broadband networks will require more time and investment for serving whole areas, but then provide higher bandwidth. Thus VDSL and G.fast Vectoring each are an interim solution. This paper highlights the benefits of such solution and the regulatory challenges and options being faced. The Virtual Unbundled Local Access (VULA) is one regulatory tool forming a compromise between the advantages of physical unbundling and the need to early satisfy higher bandwidth supply targets.
Keywords: 330; Access regulation; market 4; VDSL; Vectoring; G.fast; VULA